A new CCCH-type zinc finger-related lncRNA signature predicts the prognosis of clear cell renal cell carcinoma patients - Shen, Cheng; Chen, Zhan; Jiang, Jie; Zhang, Yong; Xu, Wei; Peng, Rui; Zuo, Wenjing; Jiang, Qian; Fan, Yihui; Fang, Xingxing; Zheng, Bing (Frontiers in Genetics, 2022)
The significance of CCCH-type zinc finger gene (CTZF) in cancer has been increasingly confirmed over the past few years. We constructed predictive signatures based on CCCH-type zinc finger-associated lncRNAs (CTZFLs). The risk model was verified using receiver operating characteristic (ROC) curve analysis. Kaplan-Meier method was used to analyze the overall survival (OS) of high-risk and low-risk groups. Multivariate Cox and stratified analyses were used to assess the prognostic value of the predictive feature in the entire cohort and different subgroups. In addition, the relationship between risk scores, immunological status, and treatment response was studied. We came to a conclusion: A Eight-CTZFLs prognostic signature may be a useful prognostic indicator for clear cell renal cell carcinoma and may offer therapy recommendations.